Viability of Lactic Acid Bacteria Isolated from Kombucha Tea Against Low pH and Bile Salt - Puspawati, Ni Nyoman; Arihantana, Ni Made Indri Hapsari (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology), 2016)
Kombucha tea is a functional drink fermented by various types of microbes. Kombucha tea is also a source of lactic acid bacteria that can maintain the balance of the microflora of the digestive tract which can improve the health of the human body. Lactic acid bacteria can act as a probiotic if it is able to survive to the human gastrointestinal tract, where in order to reach the digestive tract, lactic acid bacteria has to be resistant to the low pH in the stomach and bile salts. The purpose of this study was to determine the level of resistance of lactic acid bacteria in kombucha tea against low pH and bile salts. This study uses 20 isolates, each of these isolates were tested to the resistance of low pH 2.0 and 0.5 % bile salts with incubation time of 4 hours. The results indicated that from 20 isolates of lactic acid bacteria that were obtained from kombucha tea, 15 isolates were resistant to low pH and 13 isolates were resistant to bile salts. The isolates have a huge potential to be developed as a probiotic candidate that can contribute greatly to the health of the digestive tract.
Keywords: kombucha tea; lactic acid bacteria; viability; low pH; bile salts